Hyperbolic valued Beurling weighted bicomplex Lebesgue spaces and some of their geometric characteristics - Toksoy, Erdem (Journal of inequalities and applications, 2024)
This study introduces hyperbolic-valued Beurling weight functions and establishes bicomplex weighted Lebesgue spaces using these weight functions. Further, it examines several geometric properties of spaces, such as B C -convexity, B C -strict convexity, and B C -uniform convexity.